2022-RA-1562-ESGO Primary ovarian large B cell lymphoma: About six rare cases. (20th October 2022) - Jellali, Amani; Chalouati, Takoua; Mansouri, Houyem; Zemni, Ines; Boujelbene, Nadia; Achouri, Leila; Rahal, Khaled
Abstract : Introduction/Background: Primary ovarian non-Hodgkin's lymphoma (NHL) is a rare disease accounting for 0.5% of all NHLs and 1.5% of all malignant ovarian neoplasms. The most common histological subtype is diffuse large B-cell lymphoma. Methodology: We retrospectively reviewed the clinical records of six patients with primary ovarian lymphoma treated at Salah Azaiz Institute from 2001 to 2021. Results: The average age of patients was 40.33 years. The main symptoms consisted of pelvic pain and abdominal distension. CA125 tumor marker level was high in one case. The mean tumor size measured with CT scan was 129, 7 mm (from 50 to 173). Extraabdominal lymphadenopathies and pleural effusion were found in one case. . Two patients had hysterectomy and bilateral salpingi-oophorectomie. Four cases underwent adnexectomy. An additional small bowel resection was needed for one case. The youngest patient, with bilateral ovarian solid mass, had a left adnexectomy and a conservative treatment on the right ovary. The final histological report was in favor of diffuse large B-cell malignant lymphoma. CD-20 and Bcl-2 were expressed in all cases and the Ki67 was higher than 50% in all cases. Tumor cells were negative for the T cell marker CD3. Four patients received post operative chemotherapy with CHOP regimen and are in total remission. The two other patients are lost to follow-up. Conclusion: Primary ovarian lymphoma is a rare disease diagnosed generally after surgery using immunohistochemistry. Its treatment is essentially based on chemotherapy.